ANALISIS TEORI BELAJAR PADA PENGGUNAAN MEDIA BULLETIN TERINTEGRASI PENDIDIKAN KARAKTER UNTUK PENINGKATAN LITERASI-NUMERASI SISWA DI SDN 9 MAMBORO - Dewi Satria Ahmar; Muhammad Fath Azzajjad (Jurnal Riset Pendidikan Dasar Dan Karakter, 2025)
This study aims to evaluate the effectiveness of applying learning theories through a bulletin media integrated with character education to improve students’ literacy and numeracy at SDN 9 Mamboro. This quantitative study involved 21 students selected randomly. Data were collected through written tests administered before (pretest) and after (posttest) the learning intervention. The analysis results showed a significant improvement, with pretest minimum–maximum scores of 22.96–58.52 increasing to 64.26–98.33 in the posttest, and the mean score rising from 38.29 to a higher level after the intervention. The pretest (8.24) and posttest (7.98) standard deviations indicate that learning outcomes remained controlled. These findings are consistent with constructivist, behaviorist, and cognitivist learning theories that support active and meaningful learning. The significance value (sig. 2-tailed) of 0.000 confirms a significant effect of the character education–integrated bulletin media on improving students’ literacy and numeracy. These results may serve as a foundation for developing innovative and sustainable instructional practices in schools.